Wind-uplift capacity of cold-formed steel interlocking claddings-Experimental and numerical investigations - Roy, Krishanu (Journal of Building Engineering, 2023)
Cold-formed steel (CFS) interlocking panels are popular in industrial and housing applications. They are mostly used in façades, soffits, fascia's, chimney claddings and interior feature walls. During strong wind occurrences, CFS interlocking panels are subjected to severe wind uplift or suction pressure. This is especially problematic in areas with strong prevailing winds, such as the West Coast of the United States, the United Kingdom, and New Zealand. Turbulence in the wind flow around the building causes suction pressure, which can vary both geographically and temporally. The overlap between two adjacent interlocking panels and screw fasteners is the weakest link in the interlocking cladding system, and if it fails, the entire cladding assembly can collapse. Using a Pressure Loading Actuator (PLA), an experimental programme on a series of interlocking panels was carried out under static wind uplift and cyclic pressure. A total of 24 tests were carried out and the results are presented in this paper. The experimental investigation took into account two distinct cladding thicknesses (0.48 mm and 0.55 mm). Tensile coupon tests were used to determine the material properties of the interlocking panels, and a laser scanner was used to measure initial geometric imperfections. The load at critical tek screws was measured using 3-axis (x-y-z) and S-type load cells to determine the failure load at the screw fastener (tek screw). The interlocking panels revealed local failure around the tek screws where two adjacent cladding sheets were linked, followed by global failure of the cladding assembly at ultimate wind pressure, according to tests. A nonlinear finite element model for interlocking panels under static wind uplift pressure was also created, and the results were in good agreement with the experimental results. The finite element model contained non-linear material properties and initial imperfections. The influence of thickness, yield stress, and interlocking cladding span on the wind uplift capacity of such claddings was investigated using 264 finite element models in a parametric study. For interlocking panels' ultimate limit state of failure, load-span tables are also proposed. •Experimental tests on interlocking claddings under static wind uplift and cyclic pressure.•A total of 24 full scale wind load tests were conducted and reported herein.•A nonlinear finite element model was also developed for interlocking claddings under static wind uplift pressure.•A parametric study was conducted comprising 264 finite element models to investigate the effect of different parameters.•Load-span tables were also proposed for ultimate limit state of failure for interlocking claddings.